(untitled) (Journal of actual problems of jurisprudence, 2018)
The aim of this work is comparison of the current and lapsed legislation that is governing the use and protection of groundwater. Comparison should be directed at identifying revisions (changes) in the legislation due to an increase in the effectiveness of the protection and use of groundwater considering Kazakhstan’s transition to «green economy». The methodology of the work amounted to the dialectical method, comparative, monographic and research methods. The results of the work is concluded, that the legislation is gradually changing for the better, the rule of law and protection of groundwater use are improved. In addition, other activities are conducted with the goal to improve the efficient use of groundwater, including consolidation of the public authorities responsible for search and scouting work. The field of application of the results obtained by the author is a further improvement of the legislation on protection and use of groundwater. Key words: legal regulation of groundwater, green economy, water law, the right of subsoil use, water resources, the protection and use of groundwater.